Experience in teacher training skills in initial training for improving the climate of coexistence and prevention of school violence - Nail Kröyer, Óscar (2016)
The following speech proposes the advantages to develop teaching skills in the initial training for improving the climate of coexistence and prevention of school violence, through the analysis of critical incidents in real contexts.